Optimization Simulation of Mooring System of Floating Offshore Wind Turbine Platform Based on SPH Method - Weibo Du; Peigang Jiao; Kangning Li; Jiaming Ding (Energy Science & Engineering)
ABSTRACT In this paper, the Smoothed Particle Hydrodynamics method is used to simulate the dynamic response of the floating offshore wind turbine mooring system in a complex marine environment by using its advantages of dealing with free surface flow and fluid–structure interaction. The single‐cable mooring system and the double‐cable mooring system are introduced into the numerical simulation model of fluid–solid coupling interaction. The first‐order irregular wave and the second‐order regular wave are used to simulate different wave conditions. The operating state of the platform in these two cases is analyzed, and the accurate data such as the velocity change of the geometric center of the platform and the change of six degrees of freedom are obtained. Using visual processing and data analysis, it is found that the optimized double‐cable mooring system structure improves the vibration reduction ability of the platform.